2018
DOI: 10.1002/adma.201803339
|View full text |Cite
|
Sign up to set email alerts
|

Oxidizing Vacancies in Nitrogen‐Doped Carbon Enhance Air‐Cathode Activity

Abstract: Oxidizing vacancies in nitrogen‐doped carbon have recently been reported to enhance the oxygen reaction activity of air cathodes, but their specific role has remained elusive and controversial. Herein, the critical role of oxidizing the vacancies in enhancing the oxygen reduction reaction for metal–air battery is identified with density functional theory. Deliberate introduction of oxygen‐enriched vacancies in nitrogen‐doped carbon is shown experimentally to provide superior oxygen reduction activity. In situ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 33 publications
2
47
0
Order By: Relevance
“…The high‐resolution N 1s peak in Figure 3c could be fitted into four peaks centered at 398.3, 399.3, 401.1, and 403.8 eV, representing the pyridinic N (N1), pyrrolic N (N2), graphitic N (N3), and oxidized N (N0), respectively. [ 45,46 ] Among them, the pyridinic and graphitic N formed the catalytic active sites. [ 16,47 ] NPMRC‐900 showed the highest percentage of the pyridinic and graphitic N (Figure S10b, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high‐resolution N 1s peak in Figure 3c could be fitted into four peaks centered at 398.3, 399.3, 401.1, and 403.8 eV, representing the pyridinic N (N1), pyrrolic N (N2), graphitic N (N3), and oxidized N (N0), respectively. [ 45,46 ] Among them, the pyridinic and graphitic N formed the catalytic active sites. [ 16,47 ] NPMRC‐900 showed the highest percentage of the pyridinic and graphitic N (Figure S10b, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the H 2 O 2 yield of NPMRC‐900 was less than 10% at ≈0.4–0.9 V, indicative of high selectivity of the oxygen reduction reaction toward H 2 O. [ 46,52 ]…”
Section: Resultsmentioning
confidence: 99%
“…As illustrated in the theoretical ORR and OER volcano plots, the N‐doped defect A7 site was identified as the most active for ORR, and the dopant‐free carbon defect A6 showed the highest OER activity (Figure e). In a recent study, the oxygen‐induced vacancies in an N‐doped nanocarbon were claimed critical for improving the ORR activity of the air electrode . Combined DFT calculations and experimental studies suggested that the oxygen‐induced vacancies can deliver better ORR activity than bare nitrogen doping in the basal plane.…”
Section: Carbon‐based Bifunctional Oxygen Catalystsmentioning
confidence: 99%
“…), transition metals (Fe, Co, Ni, Zn, etc.) are introduced to replace Mo/C atoms in Mo x C. It can adjust the intrinsic electron configuration of molybdenum carbide and improve the conductivity (Li et al, 2019c;Wang et al, 2019c,f;Zhong et al, 2019).…”
Section: Dopingmentioning
confidence: 99%